2020
DOI: 10.2196/17270
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Ascure Smoking Cessation Program: Retrospective Study

Abstract: Background Smoking cessation helps extend a healthy life span and reduces medical expenses. However, the standard 12-week smoking cessation program in Japan has several notable problems. First, only 30% of participants complete this program. Second, participants may choose not to participate unless they have a strong motivation to quit smoking, such as health problems. Third, the program does not provide enough support during the period between clinical visits and after 12 weeks. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Reasons for this, and whether there are reasons common to substance and nonsubstance reward, remain elusive. Although much effort has been devoted to developing clinical programs including technology‐based therapies (e.g., Gustafson et al., 2014; Kato et al., 2020; reviewed in Newman et al., 2011; Haskins et al., 2017), the lack of mechanistic understanding of the undesired addictive habit is an obstacle for further improvement. Computational modeling has become a powerful approach to elucidating the mechanisms of psychiatric disorders including addiction (Huys et al., 2016; Kato et al., 2020; Montague et al., 2012; Wang & Krystal, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for this, and whether there are reasons common to substance and nonsubstance reward, remain elusive. Although much effort has been devoted to developing clinical programs including technology‐based therapies (e.g., Gustafson et al., 2014; Kato et al., 2020; reviewed in Newman et al., 2011; Haskins et al., 2017), the lack of mechanistic understanding of the undesired addictive habit is an obstacle for further improvement. Computational modeling has become a powerful approach to elucidating the mechanisms of psychiatric disorders including addiction (Huys et al., 2016; Kato et al., 2020; Montague et al., 2012; Wang & Krystal, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…First, overall smoking cessation success rates by the Linkage telemedicine smoking cessation programme were favourable in both short- and long-term periods: 55.8% for CAR9-24 and 42.4% for CAR9-52. Kato et al previously reported the effectiveness of the 6-month online smoking cessation programme in Japan for conventional cigarette smokers using online mentoring by trained smoking cessation experts, over-the-counter nicotine patches for medication, and a unique smartphone app 11 . They found that the CAR9-12 and CAR21-24 of patients who received the ascure online program were 48.6% and 47.5%, respectively, which were almost consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, nicotine-dependent patients, including HTP users, are eligible for a 12-week standard smoking cessation treatment programme with clinic visits and an initial screening interview in which their exhaled carbon monoxide levels are checked 10 . Moreover, some commercial telemedicine smoking cessation programmes are available for members of corporate health insurance societies (a public body that provides health insurance to corporation employees) 11 . However, biochemically check smoking cessation status through exhaled carbon monoxide, which is currently measured at every visit in a standard smoking cessation programme, is not effective for HTP use 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although much effort has been devoted to developing clinical programs including technology-based therapies (e.g. (Gustafson et al , 2014; Kato et al , 2020b); reviewed in (Newman et al , 2011; Haskins et al , 2017)), the lack of mechanistic understanding of the undesired habit is an obstacle for further improvement. Computational modeling has become a powerful approach to elucidating the mechanisms of psychiatric disorders including addiction (Montague et al , 2012; Wang & Krystal, 2014; Huys et al , 2016; Kato et al , 2020a).…”
Section: Introductionmentioning
confidence: 99%